PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN POMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN SEPEDA MOTOR HONDA VARIO DI UNIVERSITAS STIKUBANK (UNISBANK) SEMARANG) - Digo Alifandi, 11.05.51.0080 (Students Journal of Economic and Management, 2015)
The purpose of this study was to analyze the effect of product quality and percived on purchased decisions Unisbank student Semarang Vario Honda motorcycles.the population in this study is the user Vario Honda motorcycle. The samples in this study were student at the University Stikubank (Unisbank), Jl. Tri Lomba Juang Dan Jl. Kendeng V Bendan Ngisor, Semarang, user Honda Vario. The samples in this study using a non probality sampling the sampling method used is purposive sampling, the sampling technique with the goal FEB Students who use Honda Vario. The analytical tool used is multiple linear regression analysis. The result ot the analysis can be conclude that : (a) the quality of the products has a positive effect on purchasing decisions on the purchase of student Unisbank Semarang Vario HondaÂ motorcycle. (b) perceive price has a positive effect on purchasing decisions on the purchase of student Unisbank Semarang Vario Honda motorcycle. (c) promotion does not affect the purchase decision of student Unisbank Semarang Vario HondaÂ motorcycle. Keywords : quality of produk, price perceptions, promotion and purchase decisions